Implementasi Nilai-Nilai Al-Qur'an Dan Hadits Dalam Kehidupan Sehari-Hari Di SMK Negeri 1 Probolinggo : Studi Tentang Pengembangan Karakter Islami Siswa - Mohammad Nurhamsalim; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to identify and analyze the implementation of Al-Qur'an and Hadith messages in daily life at SMKN 1 Probolinggo. Through a qualitative approach with a case study method, this research explores how Islamic values are applied in school routines, including by students, teachers, and educational staff. Data was collected through interviews, observations, and documentation. The results of the study show that the Al-Qur'an and Hadith messages serve as the foundation for shaping students' character, particularly in terms of discipline, hard work, and honesty. Routines such as congregational prayer, weekly religious studies, and the application of noble character values are concrete evidence of the integration of Islamic teachings into the school's education system. This study provides practical and theoretical contributions to the development of an Islamic values-based education model.